Theoretical foundations of the use of e-government technologies in normative activity of executive authorities - Kisialiova Tatsiana М. (Journal of the Belarusian State University. Law, 2019)
The article deals with the problems of using e-government tools as a way to improve the norm-setting activity of executive bodies. The importance of ensuring the involvement of citizens in such activities is underlined. Recommendations are proposed for improving norm-setting activities taking into account the goals of building e-government.